2021
DOI: 10.1111/jfd.13502
|View full text |Cite
|
Sign up to set email alerts
|

Integration of RNA‐seq and RNAi reveals the contribution of znuA gene to the pathogenicity of Pseudomonas plecoglossicida and to the immune response of Epinephelus coioides

Abstract: Pseudomonas plecoglossicida is an important pathogen in aquaculture and causes serious economic losses. Our previous study indicated that znuA gene might play an important role in the pathogenicity of P. plecoglossicida. Five shRNAs were designed and synthesized to silence the znuA gene of P. plecoglossicida. Two of the five mutants of P. plecoglossicida exhibited significant reduction in the expression level of znuA mRNA with different efficiencies. The mutant with the highest silencing efficiency of 89.2% wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…It was found that ZnuC is an important protein for Zn uptake in Pseudomonas aeruginosa ( Huang et al, 2021 ). Similarly, the authors found that silencing the znuA gene in this strain could achieve an 89.2% reduction of deaths and that RNAi-treated strains also induced antibody production in grouper ( He et al, 2021 ). We have summarized some genes that we expect to enhance host defense through RNAi technology ( Table 1 ).…”
Section: Rnai-mediated Inhibition Of Pseudomonasmentioning
confidence: 77%
“…It was found that ZnuC is an important protein for Zn uptake in Pseudomonas aeruginosa ( Huang et al, 2021 ). Similarly, the authors found that silencing the znuA gene in this strain could achieve an 89.2% reduction of deaths and that RNAi-treated strains also induced antibody production in grouper ( He et al, 2021 ). We have summarized some genes that we expect to enhance host defense through RNAi technology ( Table 1 ).…”
Section: Rnai-mediated Inhibition Of Pseudomonasmentioning
confidence: 77%
“…Bacterial growth curves were drawn according to He et al. (2021) with some modifications. The bacteria were cultured overnight to exponential phase.…”
Section: Methodsmentioning
confidence: 99%
“…Knocked-down strains of A. salmonicida SRW-OG1 znuA, znuB and znuC were constructed using RNAi, according to the method described by Bittel et al ( 34 )and Girard et al ( 35 , 36 ) with slight modifications. The sequence of A. salmonicida SRW-OG1 znuA, znuB and znuC genes were introduced into Invitrogen Block-iT TM RNAi Designer ( https://rnaidesigner.thermofisher.com/rnaiexpress/design.do ) to design shRNA online ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%